2018
DOI: 10.1016/j.arth.2018.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Certificate-of-Need State Laws and Total Knee Arthroplasty

Abstract: CON programs appear to have influenced the delivery of care for TKA. Although our data suggest that these laws are associated with lower per capita utilization of TKA and the use of higher-volume facilities, we were unable to detect any strong evidence that CON regulations have been associated with improved quality of care or have limited growth in the utilization of this procedure over time. Confounding population and geographic factors may influence these findings and further study is needed to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Most prior studies were based on data that are 2 decades old, have focused on cardiac procedures, and examined limited outcomes such as mortality and hospital procedural volume. [2][3][4]10,11,[36][37][38] Less is known regarding the effect of certificate of need on clinical outcomes (eg, surgical site infection, readmission) or the concentration of cases within states. One study, evaluating No differences remained significant at the P < .005 level or after adjusting for 11 tests using the Bonferroni method (lower P < .05 to P < .005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most prior studies were based on data that are 2 decades old, have focused on cardiac procedures, and examined limited outcomes such as mortality and hospital procedural volume. [2][3][4]10,11,[36][37][38] Less is known regarding the effect of certificate of need on clinical outcomes (eg, surgical site infection, readmission) or the concentration of cases within states. One study, evaluating No differences remained significant at the P < .005 level or after adjusting for 11 tests using the Bonferroni method (lower P < .05 to P < .005).…”
Section: Discussionmentioning
confidence: 99%
“…The current literature regarding the clinical implications of certificate of need remains limited. Most prior studies were based on data that are 2 decades old, have focused on cardiac procedures, and examined limited outcomes such as mortality and hospital procedural volume . Less is known regarding the effect of certificate of need on clinical outcomes (eg, surgical site infection, readmission) or the concentration of cases within states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies of 1990s data have reported that higher CABG mortality rates in non-CON states (Vaughan-Sarrazin et al 2002;Rosenthal and Sarrazin 2001). Related studies include (Browne et al 2018;Casp et al 2019;Ettner et al 2020;Herb et al 2021;Ohsfeldt and Li 2018;Rahman et al 2016;Schultz et al 2021;Stratmann and Wille 2016;Wu et al 2019;Yuce et al 2020;Ziino et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Use of CON legislation varies by state; in CON states, a state agency is required to authorize healthcare network or hospital expansions. 3…”
mentioning
confidence: 99%